2019
DOI: 10.1080/2090598x.2019.1703278
|View full text |Cite
|
Sign up to set email alerts
|

Inter-observer variability amongst surgeons and radiologists in assessment of Guy’s Stone Score and S.T.O.N.E. nephrolithometry score: A prospective evaluation

Abstract: Objective: (a) To assess the inter-observer variability amongst surgeons performing percutaneous nephrolithotomy (PCNL) and radiologists for the Guy's Stone Score (GSS) and S.T.O.N.E. (stone size [S], tract length [T], obstruction [O], number of involved calyces [N], and essence or stone density [E]) nephrolithometry score; (b) To determine which scoring system of the two is better for predicting the stone-free rate (SFR) after PCNL. Patients, subjects and methods: Patients undergoing PCNL between February 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The overall S.T.O.N.E score showed good agreement between surgeons and radiologists (Fleiss К = 0.79) the same applies to Guy's score for all grades with moderate to very good agreement (Fleiss К: Grade I = 0.91; Grade 2: 0.53; Grade 3: 0.61; Grade 4: 0.84). 22 We were the only publication in our field to externally validate our data, ensuring the accuracy and reliability of our findings. This process involved an independent third-party review to verify the methodology and results, and by taking this extra step, we were able to provide further creditability to our conclusions.…”
mentioning
confidence: 89%
“…The overall S.T.O.N.E score showed good agreement between surgeons and radiologists (Fleiss К = 0.79) the same applies to Guy's score for all grades with moderate to very good agreement (Fleiss К: Grade I = 0.91; Grade 2: 0.53; Grade 3: 0.61; Grade 4: 0.84). 22 We were the only publication in our field to externally validate our data, ensuring the accuracy and reliability of our findings. This process involved an independent third-party review to verify the methodology and results, and by taking this extra step, we were able to provide further creditability to our conclusions.…”
mentioning
confidence: 89%
“…Srivastava et al also evaluated the effect of interobserver variability between surgeons and radiologists for Guy's and S.T.O.N.E scores and studied the agreement using the Fleiss coe cients. The overall S.T.O.N.E score showed good agreement between surgeons and radiologists (Fleiss = 0.79) the same applies to Guy's score for all grades with moderate to very good agreement (Fleiss : Grade I = 0.91; Grade 2: 0.53; Grade 3: 0.61; Grade 4: 0.84) [19].…”
Section: Discussionmentioning
confidence: 61%
“…Hence this score can be set as a protocol for routine scheduling PCNL and not just for research papers. Landis and Koch suggested that this score is 86% reproducible among different observers of this scoring system 20,[30][31][32] . GSS is a better way to accurately predict outcomes, especially stone clearance, whether it is calculated via ultrasound KUB, X-ray KUB, or CT-KUB 33 .…”
Section: Discussionmentioning
confidence: 96%
“…GSS IV, is worse than simple stones of GSS I. Concurrently, there was confusion in classifying GSSII and GSSIII as difficult anatomy is not equally understandable. Moreover, there was a lack of a unified definition for partial staghorn stones 30 . Despite that, the GSS is a convenient, fast, and practically possible way for grading the complexity of stones before going for PCNL.…”
Section: Discussionmentioning
confidence: 99%